Phenotypic and Multi-Omics Characterization of Escherichia coli K-12 Adapted to Chlorhexidine Identifies the Role of MlaA and Other Cell Envelope Alterations Regulated by Stress Inducible Pathways in CHX Resistance - Gregorchuk, Branden S. J.; Reimer, Shelby L.; Green, Kari A. C.; Cartwright, Nicola H.; Beniac, Daniel R.; Hiebert, Shannon L.; Booth, Timothy F.; Chong, Patrick M.; Westmacott, Garrett R.; Zhanel, George G.; Bay, Denice C. (Frontiers in Molecular Biosciences, 2021)
Chlorhexidine (CHX) is an essential medicine used as a topical antiseptic in skin and oral healthcare treatments. The widespread use of CHX has increased concerns regarding the development of antiseptic resistance in Enterobacteria and its potential impact on cross-resistance to other antimicrobials. Similar to other cationic antiseptics, resistance to CHX is believed to be driven by three membrane-based mechanisms: lipid synthesis/transport, altered porin expression, and increased efflux pump activity; however, specific gene and protein alterations associated with CHX resistance remain unclear. Here, we adapted Escherichia coli K-12 BW25113 to increasing concentrations of CHX to determine what phenotypic, morphological, genomic, transcriptomic, and proteomic changes occurred. We found that CHX-adapted E. coli isolates possessed no cross-resistance to any other antimicrobials we tested. Scanning electron microscopy imaging revealed that CHX adaptation significantly altered mean cell widths and lengths. Proteomic analyses identified changes in the abundance of porin OmpF, lipid synthesis/transporter MlaA, and efflux pump MdfA. Proteomic and transcriptomic analyses identified that CHX adaptation altered E. coli transcripts and proteins controlling acid resistance (gadE, cdaR) and antimicrobial stress-inducible pathways Mar-Sox-Rob, stringent response systems. Whole genome sequencing analyses revealed that all CHX-resistant isolates had single nucleotide variants in the retrograde lipid transporter gene mlaA as well as the yghQ gene associated with lipid A transport and synthesis. CHX resistant phenotypes were reversible only when complemented with a functional copy of the mlaA gene. Our results highlight the importance of retrograde phospholipid transport and stress response systems in CHX resistance and the consequences of prolonged CHX exposure.